The macrophage mannose receptor regulate mannan-induced psoriasis, psoriatic arthritis, and rheumatoid arthritis-like disease models - Cecilia Hagert; Outi Sareila; Tiina Kelkka; Sirpa Jalkanen; Rikard Holmdahl (Frontiers Media S.A., 2025)
The injection of mannan into mice can result in the development of psoriasis (Ps) and psoriatic arthritis (PsA), whereas co-injection with antibodies toward collagen type II leads to a chronic rheumatoid-like arthritis. The critical event in all these diseases is mannan-mediated activation of macrophages, causing more severe disease if the macrophages are deficient in neutrophil cytosolic factor 1 (Ncf1), i.e., lack the capacity to make a reactive oxygen species (ROS) burst. In this study, we investigated the role of one of the receptors binding mannan; the macrophage mannose receptor (MR, CD206). MR is a C-type lectin present on myeloid cells and lymphatics. We found that mice deficient in MR expression had more severe mannan-induced Ps, PsA as well as rheumatoid-like arthritis. Interestingly, the MR-mediated protection was partly lost in Ncf1 mutated mice and was associated with an type 2 macrophage expansion. In conclusion, these results show that MR protects against a pathogenic inflammatory macrophage response induced by mannan and is associated with induction of ROS.